The Last Natural Man : Where Have We Been and Where Are We Going? - Norman, Robert A.; Paul, Sharad P. (Springer International Publishing : Imprint: Springer, 2017)
This book describes a paradigm shift for all of humanity- we are at a point where we may be the last generation that is still partially or fully natural. We are often balancing on the precipice between science and science fiction, now ready to tip the scales and slide comfortably into the future of great discoveries and wonderful changes. Many crucial and important questions are addressed in the pages of this book, including: what are the true medical and social problems facing us? Which are the highest value targets we need to focus on to ensure our best route of success? How can we protect our futures and enhance our lives by understanding what it means to be the "last natural humans" to roam this planet? The Last Natural Man combines a fascination with the history of medicine, evolutionary biology, and medical anthropology and mix it with modern medicine and science to investigate how we evolved and where we are headed. The overall result is a clear and engaging guidebook for navigating the often confusing and cloudy waters of the future of medicine and our life on Earth.